Apical periodontitis and incident cardiovascular events in the Baltimore Longitudinal Study of Ageing. (11th June 2015) - Gomes, M. S.; Hugo, F. N.; Hilgert, J. B.; Sant'Ana Filho, M.; Padilha, D. M. P.; Simonsick, E. M.; Ferrucci, L.; Reynolds, M. A.
Abstract: Aim: To evaluate whether the presence of apical periodontitis (AP), root canal treatment (RCT) and endodontic burden (EB) – as the sum of AP and RCT sites – were associated with long‐term risk of incident cardiovascular events (CVE), including cardiovascular‐related mortality, using data on participants in the Baltimore Longitudinal Study of Ageing (BLSA). Methodology: This retrospective cohort included 278 dentate participants in the BLSA with complete medical and dental examinations. Periodontal disease (PD) and missing teeth were recorded. The total number of AP and RCT sites was determined from panoramic radiographs. EB was calculated as the sum of AP and RCT sites. Oral inflammatory burden (OIB) was calculated combining PD and EB. The main outcome was incident CVE including angina, myocardial infarction and cardiovascular‐related death. Participants were monitored for up to 44 years (mean = 17.4± 11.1 years) following dental examination. Relative risks (RRs) were calculated through Poisson regression models, estimating the relationship between AP, RCT, EB, PD, OIB and incident CVE. Results: Mean age at baseline was 55.0 ±16.8 years and 51.4% were men. Sixty‐two participants (22.3%) developed CVE. Bivariate analysis showed that PD, EB, number of teeth and OIB were associated with incident CVE. Multivariate models, adjusted for socio‐demographic and medical variables, showed that age ≥60 years (RR = 3.07, 95% CI =1.68–5.62), hypertension (RR = 2.0, 95% CI = 1.16–3.46) and EB ≥3 (RR = 1.77, 95% CI = 1.04–3.02) were independently associated with incident CVE. The association between OIB and incident CVE was reduced to nonsignificance after adjustments (RR = 1.97, 95% CI = 0.83–4.70). Conclusions: EB in midlife was an independent predictor of CVE amongst community‐dwelling participants in the BLSA. Prospective studies are required to evaluate cardiovascular risk reduction with the treatment of AP. Abstract : View the pubcast on this paper athttp://www.scivee.tv/node/63807